Situational Analysis and Gender and Social Inclusion Strategy: Towards the making of gender and youth smart innovations in Ghana - Obeng, Faustina; Damba, Osman Tahidu; Yeboah, Stephen; Dalaa, Mustapha Alasan; Huyer, Sophia; Tepa-Yotto, Ghislain (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The working paper presents AICCRA Ghana's situational analysis on differential access to and use of agriculture resources in intervention communities and highlight our strategy to mainstream gender and social inclusion into AICCRA's innovations. Through a traingulation of data from literature review, needs assessments, and baseline study, the document discusses gender and generational differences in access to and use of land, labour, capital, extensions services and participation in farmer based organisations. The document highlights how the identified gender and generational gaps are rooted in community norms and customs that define who has access to what resources under what conditions. Resulting from the situational analysis, the document presents a strategy to mainstream gender and social inclusion that builds on two main pillars: 1.Capacitation of AICCRA partners/collaborators, and farmers in communities, households and organised groups to improve access and use of Climate Smart Agriculture (CSA) and Climate Information Services (CIS) 2. Transformational dialogues with partners/collaborators and communities to reflect and change norms that entrech gender and generational inequalties.